Effects of different goal orientations and virtual opponents performance level on pacing strategy and performance in cycling time trials - Crivoi do Carmo, E.; Renfree, A.; Nishimura Vieira, C. Y.; dos Santos Ferreira, D.; Truffi, G. A.; Barroso, R. (European Journal of Sport Science, 2022)
We investigated the effects of different performance goals (best time vs. beat the opponent) on pacing behaviour during a 10-km cycling race and explored the influence of different performance level of opponents on ratings of perceived exertion (RPE), affective feelings and self-efficacy. Thirteen cyclists performed two time-trials (TT) and two races against a faster (FAST +6%) or a slower (SLOW -3%) virtual opponent. Power output (PO), RPE, affective feelings and self-efficacy were recorded at each kilometre point. Race average and race phases [starting (P1 = first kilometre); first half (P2 = 2nd-5th kilometre); second half (P3 = 6th-9th kilometre) and final sprint (FS = last kilometre)] were analysed. There was no difference in performance, assessed by race time between conditions (p = .84). PO during TT was lower in P3 compared to FS (p = .03; ES 0.6; 90%CI 0.4-0.7). In SLOW and FAST, PO was higher in P1 compared to other phases (p < .05). PO in FS was higher in TT compared to FAST (p = .01; ES -0.97; 90%IC -1.4 to -0.5). RPE increased and affective feelings decreased during all conditions. Self-efficacy was stable through TT and SLOW, but decreased during FAST with higher values in P1 compared to P2 (p = .01; ES -1.1; 90%IC -1.6 to -0.6), P3 (p < .001; ES -2.2; 90%IC -2.8 to -1.6) and FS (p < .001; ES -2.6; 90%IC -3.3 to -1.8). Pacing behaviour, specifically starting and final sprint, was affected by virtual opponents independent of performance level, demonstrating the importance of goal orientation.